Development of Batik Village Culture as A Unique Tourist Destination in Jakarta - Setiawan, Eko Adhy; Widjaja, Hinijati (Global Education Journal, 2025)
This study explores the development of Batik Village Culture as a unique urban tourist destination in Jakarta, focusing on how traditional batik craftsmanship can be preserved and revitalized within a modern metropolitan context. The research aims to analyze the strategies, challenges, and socio-cultural impacts of transforming Jakarta’s batik villages into centers of creative-based tourism that combine cultural preservation with economic empowerment. Using a qualitative descriptive method, data were collected through in-depth interviews, field observations, and documentation from artisans, government officials, and tourism stakeholders. The findings reveal that the Batik Village initiative effectively fosters community participation, strengthens local identity, and stimulates creative entrepreneurship, yet faces constraints related to policy coordination, marketing limitations, and authenticity management. The study concludes that sustaining urban cultural tourism requires adaptive collaboration between stakeholders and continuous innovation that respects traditional values. Its contribution lies in providing a model of how cultural heritage can evolve within the creative economy framework, offering insights for sustainable urban tourism development.